Understanding Ag Awareness Programming throughout UF/IFAS Extension: Supporting Citizen Awareness of Food Systems and the Environment - Joy N. Rumble; Kathryn A. Stofer; Libbie Johnson (EDIS, 2016)
Florida Extension agents around the state are working to increase public agricultural awareness (Ag Awareness). This 5-page fact sheet outlines Florida’s recent Extension efforts in agricultural awareness and highlights future directions to coordinate and strengthen this work, offering ideas for best practices while avoiding unnecessary duplication. Written by Joy N. Rumble, Kathryn A. Stofer, and Libbie Johnson, and published by the Department of Agricultural Education and Communication, April 2016.